Verbally Highlighting Extrinsic Causes of Novel Social Disparities Helps Children View Low-Status Groups as Structurally Disadvantaged Rather Than Personally Inferior - Peretz-Lange, Rebecca; Muentener, Paul (Frontiers in Psychology, 2021)
As part of their “essentialist” intuitions, young children tend to form personal attributions for observed intergroup differences – attributing them to groups’ intrinsic natures or inborn characteristics. Much research has linked this essentialist view of social groups with prejudiced attitudes. However, less research has explored children’s capacity to form structural attributions for observed intergroup differences – attributing them to groups’ extrinsic circumstances or access to opportunities – or how structural attributions relate to social attitudes. Structural attributions could enable children to view low-status groups as extrinsically disadvantaged rather than intrinsically inferior. We were interested in whether verbally highlighting the extrinsic causes of novel social status disparities could support young children in forming structural attributions for them, thereby mitigating the formation of prejudice toward novel low-status groups. To investigate, we introduced participants (n = 106 5- and 6-year-olds) to novel social status disparities that could be attributed to either intrinsic or extrinsic causes, and we framed the disparities in either intrinsic, neutral, or extrinsic terms. We then assessed children’s attributions for the disparities (through two measures: explanations and interventions) and their social attitudes toward the groups (through two measures: friendship preferences and prize allocations). Results indicated that participants tended to provide mostly personal attributions overall, but that extrinsic framing led them to provide significantly more structural attributions. Extrinsic framing did not significantly impact social attitudes overall, but exploratory analyses revealed that it impacted participants’ friendship preferences in particular. Together, results suggest that verbally highlighting extrinsic causes can disrupt children’s intuitive tendency toward personal attributions, with promising implications for their views of low-status groups.